Remote Sensing of Environment Integrated Approaches - Hadjimitsis, Diofantos G. (IntechOpen, 2013)
This book covers the latest developments in remote sensing theory and applications by numerous researchers, experts and collaborators of the Remote Sensing and Geo-Environment Lab of the Department of Civil Engineering and Geomatics of the Cyprus University of Technology. The main highlight of this book is combination of several techniques such as satellite remote sensing, field spectroscopy, smart sensors, ground techniques for achieving an integrated method for the systematic monitoring of the environment.